Totally Laparoscopic Resection of an Extremely Giant Hepatic Hemangioma - Veerankutty, Fadl H.; Rather, Shiraz Ahmad; Yeldho, Varghese; Zacharia, Bincy M.; TU, Shabeer Ali; B., Venugopal (The Surgery Journal, 2019)
Risk of massive intraoperative hemorrhage and the difficulty to control it makes the laparoscopic treatment of giant hepatic hemangiomas (GH) a challenge for minimally invasive hepatobiliary surgeons. Symptomatic GHs of more than 20 cm (extremely giant hepatic hemangiomas) are typically treated with an open resection. There is a paucity of literature on laparoscopic resection of extremely giant hepatic hemangiomas. We describe (with video), here, the technical nuances of pure laparoscopic resection of an extremely giant hepatic hemangioma using modified port positions and the anterior approach.
Keywords: liver hemangioma; laparoscopic liver resection; laparoscopic anterior approach; preoperative embolization; anatomical liver resection; pure laparoscopic hepatectomy